2019
DOI: 10.1111/myc.13021
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in HaCaT cells may account for the various clinical presentation caused by anthropophilic and geophilic dermatophytes infections

Abstract: Summary Background Despite the worldwide prevalence of dermatophyte infections, only a few genes are reported to be related to dermatophyte infections. In addition, the mechanism by which different ecological dermatophytes infection leads to varying intensity of inflammation remains unclear. Objectives To investigate the mechanism of varying intensity of skin inflammation caused by different ecological dermatophytes infection. Methods We infected HaCaT cells with anthropophilic and geophilic dermatophytes to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…[ 37 ] Another recent study conducted to distinguish the change in the gene expression of HaCaT (Cultured human keratinocyte) cell line following dermatophytic infection found that pro-inflammatory cytokines and chemokines triggered the infiltration of neutrophils and other immune cell to the infection site following zoophilic M gypseum infection due to the upregulated expression of genes related to immune response, while with T rubrum, metabolic pathway genes were upregulated instead immune response-related genes. [ 38 ] This corroborates with the clinical observations that in acute infections provoked by the zoophilic fungi T. mentagrophytes and M. gypseum, marked neutrophils are seen in the epidermis, whereas T. rubrum lead to chronic infections and are characterized by a mononuclear infiltrate. [ 11 ] Trichophyton-induced inflammation causes the proliferation of peripheral blood mononuclear cells (PBMC) and the production of IFN- γ and IFN- γ -positive CD4+ cells leading to a Th1 response[ 39 40 ] [ Figure 1 ].…”
Section: Host Immune Response To Dermatophytessupporting
confidence: 85%
“…[ 37 ] Another recent study conducted to distinguish the change in the gene expression of HaCaT (Cultured human keratinocyte) cell line following dermatophytic infection found that pro-inflammatory cytokines and chemokines triggered the infiltration of neutrophils and other immune cell to the infection site following zoophilic M gypseum infection due to the upregulated expression of genes related to immune response, while with T rubrum, metabolic pathway genes were upregulated instead immune response-related genes. [ 38 ] This corroborates with the clinical observations that in acute infections provoked by the zoophilic fungi T. mentagrophytes and M. gypseum, marked neutrophils are seen in the epidermis, whereas T. rubrum lead to chronic infections and are characterized by a mononuclear infiltrate. [ 11 ] Trichophyton-induced inflammation causes the proliferation of peripheral blood mononuclear cells (PBMC) and the production of IFN- γ and IFN- γ -positive CD4+ cells leading to a Th1 response[ 39 40 ] [ Figure 1 ].…”
Section: Host Immune Response To Dermatophytessupporting
confidence: 85%
“…Because dermatophytosis is not a life-threatening infection and its health impact can be relatively low, it represents a rather neglected infection in many regions. The infections with mild or moderate symptoms and chronic course are mostly caused by anthropophilic dermatophytes, which are typically localized to body areas that have higher moisture levels or are less accessible for the host immune response, e.g., skin folds, feet, and nails ( 2 4 ). On the other hand, zoophilic dermatophytes, when transmitted to a human, usually cause highly inflammatory infections located in sites directly exposed to contact with an infected animal, typically the extremities, face, and trunk ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the definition of a contra-regulated gene is an average gene that increases by IFN-γ and TNF-α treatment and decreases by PAB compared to the control, i.e., showing the opposite trend. To identify the functional changes in DEGs, a gene-ontology (GO) analysis was performed using ExDEGA software (E-Biogen Inc. Seoul, Korea) [ 18 , 19 , 20 ]. In this study, the GO categories were divided into 15 functional groups ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%